British Islam and English law a classical pluralist perspective - Nash, Patrick ca. 20./21. Jh (Law in context, 2022)
British Islam and English Law presents a novel argument about the nature and place of groups in society. The encounter with Islam has led English law to tread a line between two theoretical models, liberal individualism and multiculturalism, competing for dominance over the law of organised religion. This philosophical rivalry has generated a set of seemingly intractable conflicts between individual and community, religion and state, nation and culture. This book resurrects the long-buried theory of classical pluralism to address and resolve these tensions. Applying this to five understudied institutions that give structure and form to British Islam - banks, charities, schools, elections, clans - it outlines and justifies the reforms that would optimise the relationship between law and religion. Unflinching and unorthodox, this book places law and theory in context, employs innovative methods such as nudge theory and applied history, and provides detailed answers to hard questions about British Islam